THE CONCEPT AND FEATURES OF INSURANCE ASSISTANCE - Грабовська, Ганна Миронівна; Якименко, Іван Анатолійович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2019)
Purpose: in the article the author analyzes the existing approaches in the science of social security law to the understanding of the concept of «insurance assistance» and defines the absence of this definition in the current legislation. In the system of compulsory state social insurance, the insurance benefit is a periodic or one-time cash payment to the insured person or to a person who has the right to this payment in the event of an insured event in order to compensate the lost income at the expense of the funds of the insurance social funds. The fact of the importance of developing and improving the social insurance system will update the research in this area, since compulsory state social insurance must ensure the realization by citizens of their rights and receive material assistance and social services in the provided cases, which ensures the welfare of the population. Methods: phenomenological; hermeneutic; comparative legal; sociological; logical; dialectical. Results: the content of the concept «insurance assistance» and its characteristics are determined; the correlation of the concepts of «social assistance» and «insurance assistance» is indicated. Insurance assistance occupies a special place among social benefits. These include payments from social insurance funds provided for compensation or other purposes to individuals in the event of an insurance risk for them. Discussion: the need for normative fixing of the term «insurance assistance» for the sole purpose of its application. At the same time, the necessary condition is the existence of an effective legal framework that would fully regulate the specified sphere of relations.